Impact of changes in land use in the flow of the Pará River Basin, MG - Rodrigues, Evandro L.; Elmiro, Marcos A. T.; Braga, Francisco de A.; Jacobi, Claudia M.; Rossi, Rafael D. (Revista brasileira de engenharia agrícola e ambiental, 2015)
Plant cover plays an essential role in the maintenance and balance of the hydrological cycle, performing functions in the control of water availability, which guarantee flow permanence. The use of mathematical models is an alternative to represent the hydrological system and help in the understanding of phenomena involving the variables of the water cycle, in order to anticipate and predict impacts from potential changes in land use. In the present study, the hydrological model SWAT (Soil and Water Assessment Tool) was used to analyse the dynamics of flow and water flow in the Pará River Basin, Minas Gerais, Brazil, aiming to evaluate the impact caused by changes in land use in water availability. The adjusted model was assessed by the coefficient of efficiency of Nash-Sutcliffe (between -0.057 to -0.059), indicating high correlation and coefficient of residual mass (0.757 to 0.793) and therefore a satisfactory fit. An increase of about 10% in the basin flow was estimated, as a function of changes in land use, when simulating the removal of the original 'Cerrado' vegetation and of the seasonal semideciduous forest for pasture implementation in 38% of the basin. A cobertura vegetal exerce papel fundamental na manutenção e no equilíbrio do ciclo hidrológico, desempenhando funções no controle da produção de água que garantem a permanência de vazões. O uso de modelos matemáticos é uma alternativa para representar o sistema hidrológico e auxiliar na compreensão dos fenômenos que envolvem as variáveis do ciclo da água para antecipar impactos decorrentes de eventuais mudanças no uso da terra. Neste trabalho é utilizado o modelo hidrológico SWAT (Soil and Water Assessment Tool) para analisar a dinâmica da vazão na bacia do Rio Pará, em Minas Gerais, Brasil, com o objetivo de avaliar o impacto provocado pelas alterações de uso do solo na disponibilidade de água da bacia do Rio Pará. O ajuste do modelo foi avaliado pelo coeficiente de eficiência de Nash-Sutcliffe (entre -0,057 a -0,059) indicando alta correlação e coeficiente de massa residual (0,757 a 0,793) e, portanto, um ajuste satisfatório. Estima-se que houve incremento de cerca de 10% na vazão da bacia em função das alterações no uso do solo, contemplando basicamente a supressão da vegetação original de Cerrado e de Floresta Estacional Semidecidual para implantação de pastagem em 38% do território da bacia.